Effects of ambient temperatures between 5 and 35 °C on energy balance, body mass and body composition in mice - Zhijun Zhao; Rui Yang; Min Li; Menghuan Bao; Daliang Huo; Jing Cao; John R. Speakman (Elsevier, 2022)
Background: Considerable attention is currently focused on the potential to switch on brown adipose tissue (BAT), or promote browning of white adipose tissue, to elevate energy expenditure and thereby reduce obesity levels. These processes are already known to be switched on by cold exposure. Yet humans living in colder regions do not show lower levels of obesity. This could be because humans shield themselves from external temperatures, or because the resultant changes in BAT and thermogenesis are offset by elevated food intake, or reductions in other components of expenditure. Scope of Review: We exposed mice to 11 different ambient temperatures between 5 and 35 °C and characterized their energy balance and body weight/composition. As it got colder mice progressively increased their energy expenditure coincident with changes in thyroid hormone levels and increased BAT activity. Simultaneously, these increases in expenditure were matched by elevated food intake, and body mass remained stable. Nevertheless, within this envelope of unchanged body mass there were significant changes in body composition - with increases in the sizes of the liver and small intestine, presumably to support the greater food intake, and reductions in the level of stored fat - maximally providing about 10% of the total elevated energy demands. Major Conclusions: Elevating activity of BAT may be a valid strategy to reduce fat storage even if overall body mass is unchanged but if it is mostly offset by elevated food intake, as found here, then the impacts may be small.